Effects of macitentan and selexipag across prognostic age groups in patients with pulmonary arterial hypertension - Richard Channick, MD; Sarah Medrek, MD; Marion Delcroix, MD; Sean Gaine, MD; Pavel Jansa, MD, PhD; Irene Lang, MD; Vallerie McLaughlin, MD; Sanjay Mehta, MD; Tomas Pulido, MD; Bhagavatula Sastry, MD; Rogerio Souza, MD, PhD; Adam Torbicki, MD; et al. (JHLT Open)
BACKGROUND: Age affects disease severity and patient outcomes in pulmonary arterial hypertension. This post-hoc analysis identified prognostic age groups and associated macitentan/selexipag treatment effects. METHODS: Randomized trials evaluated macitentan (SERAPHIN; NCT00660179) and selexipag (GRIPHON; NCT01106014) versus placebo (primary endpoint: time to morbidity/mortality [M/M]). This analysis defined age thresholds differentiating M/M risk in patients randomized to placebo (Cox regression determining treatment effect by age). RESULTS: Three age groups (< 35, 35–64, ≥ 65 years) showed good M/M risk discrimination (c-statistic 0.69, SERAPHIN; 0.66, GRIPHON). M/M risk was higher in placebo patients < 35 versus 35–64 years (SERAPHIN: hazard ratio [HR] 1.73, 95% confidence interval [CI] 1.10–2.72, p = 0.02; GRIPHON: HR 1.81, 95% CI 1.28–2.56, p < 0.001). M/M risk trended higher in patients ≥ 65 versus 35–64 years (SERAPHIN: HR 1.55, 95% CI 0.89–2.69, p = 0.12; GRIPHON (HR 1.08, 95% CI 0.75–1.55, p = 0.69). M/M risk was lower with macitentan/selexipag versus placebo: macitentan < 35 (HR 0.44, 95% CI 0.25–0.78; p = 0.005), 35–64 (HR 0.50, 95% CI 0.33–0.76; p < 0.001), ≥ 65 years (HR 0.69, 95% CI 0.30–1.58; p = 0.38); selexipag < 35 (HR 0.50, 95% CI 0.32–0.78; p = 0.002), 35–64 (HR 0.72, 95% CI 0.54–0.96; p = 0.03), ≥ 65 years (HR 0.55, 95% CI 0.33–0.91; p = 0.02). Adverse-event discontinuations were similar. CONCLUSIONS: The benefit (vs placebo) of macitentan/selexipag on reducing risk of M/M events was consistent across all ages, including the younger group where significant treatment effects were observed.